Kritik Sosial dan Nilai Moral dalam Novel "Negeri dI Ujung Tanduk" Karya Tere Liye - Alvika Candra Puspita; Sarwiji Suwandi; Sri Hastuti (Indonesian Language Education and Literature)
Social criticism and moral values can be found in many literary works, especially novels. The objectives of this research are to describe: (1) social criticism and (2) moral values within the “Negeri di Ujung Tanduk” novel by Tere Liye. This research used a qualitative method as a guideline to analyze documents containing information in the novel. To collect data, a purposive sampling technique and document analysis were used considerably. Data analysis techniques used interactive analysis techniques consisting of data reduction, data presentation, as well as withdrawal and testing conclusions. The outcomes of this research include (1) the social criticism within the “Negeri di Ujung Tanduk” novel such as (a) crime, (b) family disorganisation, (c) social norm violation, dan (d) bureaucracy; and (2) Moral values within the “Negeri di Ujung Tanduk” novel such as (a) individual moral values, (b) social moral values, and (c) religious moral values. Kritik sosial dan nilai moral banyak terdapat dalam karya sastra khususnya novel. Tujuan penelitian ini adalah untuk mendeskripsikan: (1) kritik sosial dan (2) nilai moral dalam novel “Negeri di Ujung Tanduk” karya Tere Liye. Penelitian ini termasuk penelitian kualitatif yang menganalisis data berupa dokumen dengan objek kajian novel “Negeri di Ujung Tanduk” karyaTere Liye. Teknik pengambilan subjek penelitian dengan purposive sampling. Teknik pengumpulan data berupa analisis dokumen. Teknik analisis data menggunakan teknik analisis interaktif yang terdiri dari reduksi data, penyajian data, serta penarikan dan pengujian simpulan. Hasil penelitian ini dikemukakan sebagai berikut: (1) Kritik sosial yang terdapat dalam novel “Negeri di Ujung Tanduk”, meliputi (a) kejahatan, (b) disorganisasi keluarga, (c) pelanggaran terhadap norma-norma masyarakat, (d) birokrasi, dan (2) Nilai moral yang terdapat dalam novel “Negeri di Ujung Tanduk”, meliputi, (a) nilai moral individu, (b) nilai moral sosial, dan (c) nilai moral religius.